Power from powerlessness tribal governments, institutional niches, and American federalism - Evans, Laura E. (Laura Elizabeth), 1972- (New York ; Oxford : Oxford University Press, 2011)
Here, Laura Evans looks at the successful policy interventions by a range of Indian tribes to explain how disadvantaged groups can build capacity and exploit niches in the institutional framework of American federalism to obtain unlikely victories.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Indians of North America -- Politics and government; Tribal government -- United States; Indians of North America -- Government relations; Intergovernmental cooperation -- United States; Federal government -- United States